2014
DOI: 10.1017/thg.2013.85
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Etiologies of Adolescent Dysfunctional Attitudes: A Twin Study

Abstract: Despite the importance of dysfunctional attitudes in the development and maintenance of depression, little is known about the etiological origin of dysfunctional attitudes. The Dysfunctional Attitudes Scale for Children was administered to 674 adolescent twins derived from the Beijing Twin Study (BeTwiSt). Four hundred and thirty-nine monozygotic and 235 same-gender dizygotic twin pairs were included. Approximately 54% were females. The age range of the twins was 11-17 years. Model-fitting analyses were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…In line with this result, past research has indicated that maladaptive beliefs have a moderate heritable component as it has been evidenced in a sample of 674 adolescent twins, where nonshared environmental factors explained 60% of variance in maladaptive beliefs (Chen & Li, 2014).…”
supporting
confidence: 70%
“…In line with this result, past research has indicated that maladaptive beliefs have a moderate heritable component as it has been evidenced in a sample of 674 adolescent twins, where nonshared environmental factors explained 60% of variance in maladaptive beliefs (Chen & Li, 2014).…”
supporting
confidence: 70%
“…Our results indicating significant effects of the OPRM1 genotype on sociotropy and interpersonal sensitivity are in line with the results of previous twin studies on these personality traits. Namely, genetic factors accounted for 31% of variation in a group of 22 self‐schemas (Chen & Li, 2014 ), while they accounted for 27% of variation in interpersonal sensitivity (Gillespie et al., 2001 ). Incidentally, in the former study (Chen & Li, 2014 ) self‐schemas were not classified according to their contents.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, genetic factors accounted for 31% of variation in a group of 22 self‐schemas (Chen & Li, 2014 ), while they accounted for 27% of variation in interpersonal sensitivity (Gillespie et al., 2001 ). Incidentally, in the former study (Chen & Li, 2014 ) self‐schemas were not classified according to their contents. Therefore, the possibility that genetic factors had a strong effect on a cluster of interpersonal schemas (i.e., sociotropic schemas), but a weak or no effect on a cluster of impersonal schemas (i.e., autonomic schemas) cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar degree of heritability has also been used to define endophenotypes in others studies. For instance, using a twin design Chen and Li showed that the additive genetic factor accounted for 31% (i.e., A = 0.31) of variance in the endophenotype of adolescent dysfunctional attitude [Chen and Li, ]. In another study using a mother‐offspring design, the heritability of delusional‐like experiences was estimated to be 0.35 (standard error 0.04), and these experiences were considered to represent a quantitative endophenotype for genetic studies of common mental disorders [Varghese et al, ].…”
Section: Discussionmentioning
confidence: 99%